Design and Simulation Sag Tension of a 20kV Power System with 150kV Tower Infrastructure in Marabahan City with Monte Carlo method - Alviando Wisang , Muhammad; Noor Hidayat, Mohamad; Rahmad, Cahya; surya Wijaya, Wldan (BEST, 2025)
Rumpiang Bridge is a vital object and requires special handling for voltage installation; therefore, a construction that is capable of spanning a wide area is needed, where the construction obtained is the 150 kV HV construction, and for the cable span, it is simulated using the Monte Carlo method for the analysis of cable crossing deflection in Barito Kuala, with three types of cables, namely ACSR, AAAC, and AAACS. The simulation was carried out 1000 times by considering random variations of ±10% in cable weight and tensile force and ±5% in the crossing length. The results show that ACSR and AAAC cables have low average deflections, 3.24 meters and 3.26 meters, respectively, with standard deviations of 0.33 meters and 0.32 meters, indicating stable and consistent mechanical performance. While the AAACS cable shows a higher average deflection of 4.72 meters and a standard deviation of 0.48 meters, indicating a greater variation in deflection due to its physical characteristics. All three cables meet the technical requirement of maximum deflection <30 meters, but ACSR cable is recommended as the primary choice due to its combination of low deflection and high stability, which provides a greater safety margin in extreme crossing environmental conditions.